Maternal Determinants of Preeclampsia Incidence in Arjawinangun Hospital, Cirebon District, West Java: A Case Study - Nurjanah, Nunung; Pramono, Noor; -, Anggorowati; Soejoenoes, Ariawan (Journal of Nursing Care, 2025)
Most of these complications develop during pregnancy. The main complications accounting for 80% of maternal deaths are severe bleeding (mostly postpartum hemorrhage), infection (usually after delivery), high blood pressure during pregnancy (pre-eclampsia and eclampsia) and unsafe abortion. This was an analytic observational study with a case control design. The data taken were the medical records of patients diagnosed with preeclampsia from Januari to Desember 2024. The population of pregnant women at RSUD Arjawinangun, Cirebon was 2.780 pregnant women. The sample size was obtained by random sampling technique as many as 350 pregnant women in accordance with the inclusion and exclusion criteria determined for the study. The result that Age (p-value 0.001, OR 5.678), Parity (p-value 0.001, OR 2.606), Occupation (p-value 0.026, OR 2.053), Pregnancy distance (p-value 0.002, OR 2.005), Nutritional Status (p-value 0.001, OR 3.898), History of Preeclampsia (p-value 0.001, OR 14.462), MAP (p-value 0.001, OR 7.644). Age, Gravida, Interpregnancy interval, BMI, History of preeclampsia, MAP, occupation are factors contributing to the occurrence of preeclampsia in pregnant women at Arjawinangun Hospital, Cirebon Regency. Pregnant women with a history of preeclampsia have a 153.342 times higher chance of experiencing preeclampsia in their current pregnancy. Age, Gravida, Interpregnancy interval, BMI, History of preeclampsia, MAP, occupation are factors contributing to the occurrence of preeclampsia in pregnant women at Arjawinangun Hospital, Cirebon Regency.